Method for improving specific capacity of commercial carbon material and application of commercial carbon material in supercapacitor

By combining commercial carbon materials with pseudocapacitor materials and mixing them with conductive agents and binders, the problems of limited specific capacity and cycle stability of commercial carbon electrode materials are solved, and supercapacitor electrode materials with high specific capacity and excellent cycle stability are achieved. , suitable for large-scale production.

CN119252671APending Publication Date: 2025-01-03ANHUI GLANCO NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411317867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Commercial carbon electrode materials have limited specific capacity in supercapacitors, and traditional modification and improvement methods affect cyclic stability, resulting in limited energy density.

Method used

Combining commercial carbon materials with pseudocapacitor materials, improving conductivity and electrochemical reaction capabilities through in-situ modification, uniformly mixing of conductive agents and binders, coating and assemble into supercapacitors.

Benefits of technology

It significantly improves the specific capacitance and cyclic stability of commercial carbon materials, achieves high specific capacity and excellent electrochemical performance, and is simple in process, low in cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252671A_ABST
    Figure CN119252671A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the specific capacity of a commercial carbon material and application of the commercial carbon material in a supercapacitor, and relates to the technical field of supercapacitor electrode materials, and the method for improving the specific capacity of the commercial carbon material comprises the steps that the commercial carbon material and a pseudocapacitance material are compounded to obtain the improved commercial carbon material; the in-situ modification mode adopted by the invention does not change the structure of the carbon material, the conductivity of the commercial carbon material can be remarkably improved, and the purpose of improving the specific capacitance of the commercial carbon material is achieved by optimizing the electrochemical reaction of ions in the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a method for improving the specific capacity of commercial carbon materials and an application thereof in supercapacitors. Background Art

[0002] Supercapacitors are a new type of energy storage device between batteries and traditional capacitors. Designing electrode materials for supercapacitors with high specific capacity is the key to their advantages among many electrochemical energy storage devices. At present, supercapacitors can be divided into double-layer capacitors and pseudocapacitors according to the energy storage characteristics of electrode materials. The former stores energy through the physical double-layer reaction of the electrode active site, and has ultra-high charge and discharge cycle stability, but low specific capacitance; the latter stores energy through reversible redox chemical reactions of active substances on the surface of electrode materials, and has high energy density but low power density. Therefore, the key to improving the performance of supercapacitors lies in the design and optimization of the electrode material structure.

[0003] Commercial carbon electrode materials have great application potential in supercapacitor electrode materials due to their ultra-high specific surface area and theoretical specific capacity. However, due to factors such as the current preparation and processing technology and reaction conditions, the capacitance of carbon electrode materials is still difficult to reach the theoretical value, resulting in limited energy density of the assembled supercapacitors. Traditional carbon electrode material modification and improvement methods usually destroy the original carbon skeleton structure to obtain higher specific capacitance, which affects the structural continuity and conductivity of the carbon electrode material, and further causes the electrode to show obvious capacity decay during the cyclic charge and discharge process. Therefore, designing a method to improve the specific capacitance of commercial carbon electrode materials without sacrificing the structural stability is expected to further improve the energy density of supercapacitor products. Summary of the invention

[0004] In view of the problem that the specific capacity of current commercial carbon electrode materials is limited and the traditional carbon electrode material modification and improvement methods affect the cycle stability, the present invention provides a method for improving the specific capacity of commercial carbon materials, thereby achieving the purpose of significantly improving the electrochemical performance without changing the structure of the carbon material.

[0005] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0006] The first object of the present invention is to provide a method for improving the specific capacity of commercial carbon materials, by compounding commercial carbon materials with pseudocapacitive materials to obtain improved commercial carbon materials.

[0007] The second object of the present invention is to provide an improved commercial carbon material obtained by the method for improving the specific capacity of commercial carbon materials.

[0008] The third object of the present invention is to provide application of the improved commercial carbon material as electrode material.

[0009] The fourth object of the present invention is to provide a supercapacitor using the improved commercial carbon material as an electrode material.

[0010] A fifth object of the present invention is to provide a method for preparing a supercapacitor, comprising the following steps:

[0011] (1) uniformly mixing the improved commercial carbon material with a conductive agent and a binder in proportion to obtain a carbon electrode slurry;

[0012] (2) uniformly coating the carbon electrode slurry on the current collector, drying, and rolling to obtain a carbon electrode sheet;

[0013] (3) Assemble the carbon electrode sheet, diaphragm and electrolyte into a supercapacitor.

[0014] The beneficial effects of the present invention are:

[0015] (1) The in-situ modification method adopted by the present invention does not change the structure of the carbon material, but can significantly improve the conductivity of the commercial carbon material and achieve the purpose of improving its specific capacitance by optimizing the electrochemical reaction of ions inside the electrode.

[0016] (2) The present invention enables commercial carbon electrode materials to obtain enhanced electrochemical reaction capabilities through stable in-situ loading of pseudocapacitive active materials, and has the characteristics of high specific capacity and excellent cycle stability.

[0017] (3) The method provided by the present invention has the characteristics of simple process and low cost, and is expected to achieve large-scale mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM image of the oxygen-composite commercial amorphous carbon electrode powder prepared in Example 1;

[0019] Figure 2 The pore size distribution diagram of the oxygen-composite commercial amorphous carbon electrode powder prepared in Example 1;

[0020] Figure 3 The CV curve diagram of the three electrodes prepared in Example 1 in the voltage range of -0.8 to 0 V;

[0021] Figure 4 The GCD curve of the three electrodes prepared in Example 1 in the voltage range of -0.8 to 0 V;

[0022] Figure 5 The GCD curve of the three electrodes prepared in Example 2 in the voltage range of -1.2 to 0 V;

[0023] Figure 6 The surface SEM morphology of the commercial amorphous carbon electrode material composited with manganese oxide prepared in Example 3;

[0024] Figure 7 The GCD curve of the three electrodes prepared in Example 4 in the voltage range of -1.2 to 0 V;

[0025] Figure 8 The GCD curve of the three electrodes prepared in Example 5 in the voltage range of -1.2 to 0 V;

[0026] Fig. 9 A digital image of a supercapacitor prepared in Example 6;

[0027] Fig.10 This is a digital image of the supercapacitors prepared in Example 6 lighting up a 2.5V light bulb after being connected in series. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0029] The present invention provides a method for improving the specific capacity of commercial carbon materials, and the commercial carbon materials are compounded with pseudocapacitor materials to obtain improved commercial carbon materials.

[0030] Furthermore, the commercial carbon material includes but is not limited to one or more of amorphous carbon, carbon nanotubes, carbon fibers, graphite, graphene, and fullerene. Preferably, the commercial carbon material has a specific surface area of ​​>500 m 2 / g, conductivity>50S / m. Select commercial carbon materials with good conductivity and high specific surface area.

[0031] Furthermore, the pseudocapacitive material includes, but is not limited to, one or more of metal oxides, metal hydroxides, metal sulfides, conductive polymers, oxygen-containing compounds, nitrogen-containing compounds, and sulfur-containing compounds.

[0032] The composite method includes, but is not limited to, one or more of high-energy beam scanning treatment, flash Joule heat treatment, energized Joule heat treatment, hydrothermal treatment, heat treatment, and physical embedding.

[0033] The present invention provides an improved commercial carbon material obtained by the method for improving the specific capacity of commercial carbon materials.

[0034] The present invention also provides application of the improved commercial carbon material as an electrode material.

[0035] The present invention provides a supercapacitor using the improved commercial carbon material as an electrode material.

[0036] The present invention also provides a method for preparing a supercapacitor, comprising the following steps:

[0037] (1) uniformly mixing the improved commercial carbon material with a conductive agent and a binder in proportion to obtain a carbon electrode slurry;

[0038] (2) uniformly coating the carbon electrode slurry on the current collector, drying, and rolling to obtain a carbon electrode sheet;

[0039] (3) Assemble the carbon electrode sheet, diaphragm and electrolyte into a supercapacitor.

[0040] Further, the mass ratio of the improved commercial carbon material to the conductive agent and the binder is (75-90):(2-15):(2-15). Preferably, the mass ratio of the improved commercial carbon material to the conductive agent and the binder is (80-85):(5-10):(5-10).

[0041] Furthermore, the conductive agent includes but is not limited to one or more of acetylene black, conductive carbon black, graphite, Ketjen black, carbon nanotubes, graphene, and amorphous carbon.

[0042] Furthermore, the binder includes but is not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, gelatin, and polyacrylate.

[0043] Furthermore, the current collector includes but is not limited to one or more of aluminum foil, carbon-coated aluminum foil, aluminum mesh, copper foil, carbon-coated copper foil, copper mesh, nickel foil, nickel mesh, nickel foam, carbon paper, titanium foil, and titanium foam. A highly conductive current collector with a resistance of less than 0.5Ω is preferred.

[0044] Furthermore, the diaphragm is one of a biomass-based diaphragm material, a synthetic polymer diaphragm material, and an inorganic composite diaphragm material.

[0045] Further, the electrolyte is one of an aqueous electrolyte, an organic electrolyte, and an ionic electrolyte. Preferably, the electrolyte is one of a Na2SO4 solution, a LiCl solution, a H2SO4 solution, and a KOH solution.

[0046] Furthermore, the supercapacitor includes but is not limited to a button-type micro supercapacitor, a soft-pack supercapacitor, and a can-wound supercapacitor.

[0047] Furthermore, the supercapacitors are combined in series or in parallel to obtain a supercapacitor energy storage system.

[0048] The technical solution of the present invention is described in detail below through specific embodiments.

[0049] Example 1

[0050] (1) Weigh 5 g of commercial amorphous carbon material and 2 g of phenolic resin powder with an oxygen content greater than 30% into 20 mL of anhydrous ethanol, and uniformly disperse them under a magnetic stirrer at 500 r / min for 6 h to obtain a commercial amorphous carbon-dispersed phenolic resin solution.

[0051] (2) Vacuum filtration is performed on the phenolic resin solution dispersed with the commercial amorphous carbon obtained in step (1) to obtain a commercial amorphous carbon material composited with a phenolic resin.

[0052] (3) The commercial amorphous carbon material composited with phenolic resin obtained in step (2) is heat-treated at a temperature of 500° C. for 3 hours to obtain an oxygen-composite commercial amorphous carbon material.

[0053] (4) Weigh 8.4 g of the oxygen-composite commercial amorphous carbon material powder obtained in step (3) and mix it with conductive carbon black and polyvinylidene fluoride in a mass ratio of 81:5:14 under magnetic stirring at a speed of 800 r / min for 6 h to obtain an electrode slurry.

[0054] (5) The electrode slurry obtained in step (4) is coated on a carbon cloth with a thickness of 50 μm by wire rod coating, and the coating thickness is 1000 μm. After coating, it is placed in an oven at 80° C. for drying, and after complete drying, an oxygen-compounded commercial amorphous carbon electrode sheet is obtained.

[0055] (6) The oxygen-composite commercial amorphous carbon electrode sheet prepared in step (5) is placed in a double-roll press for pressing at a pressure of 10 MPa for a holding time of 5 min.

[0056] (7) The electrode sheet obtained in step (6) was cut into a size of 1.5 cm × 1.0 cm and used as a working electrode. The counter electrode was a platinum electrode, the reference electrode was a saturated silver chloride electrode, and the electrolyte was a solution of 1 M Na2SO4 and 1 M KCl mixed in a mass ratio of 1:1.

[0057] Figure 1 This is a SEM image of the oxygen-composite commercial amorphous carbon material powder prepared in Example 1. Figure 1 It can be seen that the structure of the commercial amorphous carbon material has not changed, indicating that this in-situ improvement method can enhance the interfacial bonding force of the carbon surface and promote the development of the electrode electrochemical reaction. The four-probe resistance tester shows that the resistance of the oxygen-compounded commercial amorphous carbon electrode sheet is 2.4Ω / sq, which is significantly improved compared with the resistance of 6.1Ω / sq of the commercial amorphous carbon sample without oxygen compounding, proving that this improvement method can improve the conductivity of commercial activated carbon materials.

[0058] Figure 2The pore size distribution of the oxygen-composite commercial amorphous carbon material powder prepared in Example 1. Figure 2 It can be seen that there is no obvious change in the pore structure of the commercial amorphous carbon material before and after oxygen recombination, which once again proves that the initial structure is not significantly affected by the introduction of oxygen-containing groups.

[0059] Figure 3 The CV curves of the three electrodes prepared in Example 1 in the voltage range of -0.8 to 0 V. Figure 3 It can be seen that in the potential range of 0-0.8 V, the CV curves at different scan rates have excellent cycle stability.

[0060] Figure 4 The GCD curve test of the three electrodes prepared in Example 1 in the voltage range of -0.8 to 0 V. Figure 4 It can be seen that at 5mA / cm 2 The area specific capacity calculated at the current density is 1765.2mF / cm 2 , compared with the commercial amorphous carbon material without oxygen compounding (area specific capacity 657.3mF / cm 2 ), the improved commercial activated carbon powder has a specific capacity increased by about 2.7 times.

[0061] Example 2

[0062] The preparation steps of this embodiment are the same as those of Example 1, except that: in step (1), "5 g of commercial amorphous carbon material, 2 g of phenolic resin powder with an oxygen content greater than 30% and 5 mL of 1.5 M ferric chloride aqueous solution are weighed and poured into 20 mL of anhydrous ethanol."

[0063] Figure 5 The GCD curve test of the three electrodes prepared in Example 2 in the voltage range of -1.2 to 0V. Figure 5 It can be seen that at 10mA / cm 2 The calculated area specific capacity at the current density is 3436.8mF / cm 2 , compared with the unmodified commercial amorphous carbon material (area specific capacity 657.3mF / cm 2 ), the specific capacity is increased by about 5.2 times.

[0064] Example 3

[0065] The preparation steps of this embodiment are the same as those of Example 1, except that: in step (1), "5 g of commercial amorphous carbon material, 2 g of phenolic resin powder with an oxygen content greater than 30% and 5 mL of 2M manganese acetate aqueous solution are weighed and poured into 20 mL of anhydrous ethanol."

[0066] Figure 6This is a surface SEM morphology of the commercial amorphous carbon electrode material composited with manganese oxide prepared in Example 3. Figure 6 It can be seen that the phenolic resin-derived carbon-coated manganese oxide particles are dispersed in the commercial amorphous carbon material, providing a large amount of reversible pseudocapacitive reaction for the electrode during charging and discharging, proving that this improved method is universal in the field of preparing high-stability pseudocapacitive composite graphene electrodes.

[0067] Example 4

[0068] The preparation steps of this embodiment are the same as those of embodiment 2, except that the compounding method in step (3) is flash Joule heat treatment, the voltage is 15V, the temperature is 2500°C, and the flash time is 3s.

[0069] Figure 7 This is the GCD curve of the three electrodes prepared in Example 4 in the voltage range of -1.2 to 0 V. Figure 7 It can be seen that at 10mA / cm 2 The area specific capacity calculated at the current density is 1766.67mF / cm 2 , significantly better than the unmodified commercial amorphous carbon material (area specific capacity 657.3mF / cm 2 ).

[0070] Example 5

[0071] The preparation steps of this embodiment are the same as those of Embodiment 2, except that: the composite method in step (3) is a CO2 laser high-energy beam scanning process with a power of 8 W, a scanning rate of 50 mm / s, and a scanning line spacing of 0.05 mm.

[0072] Figure 8 This is the GCD curve of the three electrodes prepared in Example 5 in the voltage range of -1.2 to 0 V. Figure 8 It can be seen that at 10mA / cm 2 The calculated area specific capacity at the current density is 1869.2mF / cm 2 , significantly better than the unmodified commercial amorphous carbon material (area specific capacity 657.3mF / cm 2 ).

[0073] Example 6

[0074] The preparation steps of this embodiment are the same as those of Example 2, except that the electrode sheet prepared in Example 2 is cut into a size of 2 cm×3 cm, and connected to the nickel-plated steel strip using conductive silver paste, and then placed in an 80°C oven for drying for 3 hours for assembling a symmetrical supercapacitor.

[0075] Biomass-based materials (NKK-MPF30AC-100) are used as the diaphragm, and the electrolyte is a solution of 1M Na2SO4 and 1M KCl mixed in a mass ratio of 1:1. A 60μm aluminum-plastic film is used as the shell, and it is sealed under a vacuum packaging machine to obtain a packaged supercapacitor. The actual picture is as follows Fig. 9 shown.

[0076] The capacitance and energy density test results of the supercapacitor test system showed that the assembled symmetrical supercapacitor had a stable operating voltage window of 1.2V and an energy density of 11.3Wh / kg. Fig.10 This is an image of two identical supercapacitors connected in series to light up a 2.5V light bulb, meeting the requirements for use in microelectronic devices.

[0077] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for increasing the specific capacity of commercial carbon materials, characterized in that: Commercial carbon materials are compounded with pseudocapacitive materials to obtain improved commercial carbon materials.

2. The method for increasing the specific capacity of commercial carbon materials according to claim 1, characterized in that: The commercial carbon material is one or more of amorphous carbon, carbon nanotubes, carbon fibers, graphite, graphene, and fullerene; preferably, the specific surface area of ​​the commercial carbon material is greater than 500 m 2 / g, conductivity>50S / m.

3. The method for increasing the specific capacity of commercial carbon materials according to claim 1, characterized in that: The pseudocapacitive material is one or more of metal oxides, metal hydroxides, metal sulfides, conductive polymers, oxygen-containing compounds, nitrogen-containing compounds, and sulfur-containing compounds.

4. The method for increasing the specific capacity of commercial carbon materials according to claim 1, characterized in that: The composite method is one or more of high-energy beam scanning treatment, flash Joule heat treatment, energized Joule heat treatment, hydrothermal treatment, heat treatment, and physical embedding.

5. An improved commercial carbon material obtained by the method for increasing the specific capacity of commercial carbon materials as described in any one of claims 1 to 4.

6. Use of the improved commercial carbon material as claimed in claim 5 as an electrode material.

7. A supercapacitor, characterized in that: The improved commercial carbon material as claimed in claim 5 is used as an electrode material.

8. A method for preparing a supercapacitor, characterized in that: The following steps are involved: (1) uniformly mixing the improved commercial carbon material with a conductive agent and a binder in proportion to obtain a carbon electrode slurry; (2) uniformly coating the carbon electrode slurry on the current collector, drying, and rolling to obtain a carbon electrode sheet; (3) Assemble the carbon electrode sheet, diaphragm and electrolyte into a supercapacitor.

9. The method for preparing a supercapacitor according to claim 8, characterized in that: The mass ratio of the improved commercial carbon material to the conductive agent and the binder is (75-90):(2-15):(2-15); Preferably, the conductive agent is one or more of acetylene black, conductive carbon black, graphite, Ketjen black, carbon nanotubes, graphene, and amorphous carbon; Preferably, the binder is one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, gelatin, and polyacrylate; Preferably, the current collector is one or more of aluminum foil, carbon-coated aluminum foil, aluminum mesh, copper foil, carbon-coated copper foil, copper mesh, nickel foil, nickel mesh, nickel foam, carbon paper, titanium foil, and titanium foam; Preferably, the diaphragm is one of a biomass-based diaphragm material, a synthetic polymer diaphragm material, and an inorganic composite diaphragm material; Preferably, the electrolyte is one of an aqueous electrolyte, an organic electrolyte, and an ionic electrolyte; Preferably, the supercapacitor is a button-type micro supercapacitor, a soft-pack supercapacitor, or a can-wound supercapacitor.

10. The method for preparing a supercapacitor according to claim 8, characterized in that: The supercapacitors are combined in series or in parallel to obtain a supercapacitor energy storage system.